Engineering and Development of Probiotics for Poultry Industry - Koshchaev, Andrey Georgievich (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: This work discusses the development of dry three-strain probiotic food additive on the basis of thermophilic lactic bacteria strains (Lactobacillus acidophilus Ð’-8634, Lactobacillus delbruÐµckii subsp. bulgaricus Ð’-6543 and Streptococcus thermophiles Ð’-2894) for the poultry industry. Materials and Methods: The pattern of interrelations between the strains in the composition of the food additive has been studied by their simultaneous inoculation on solid and liquid nutrient media, incubation and colony-forming unit count by limiting dilution method. On cultivation on solid nutrient media by-products of plant reprocessing were used as a nutrient medium carrier and mineral sorbent - as dilution agent. Antibacterial activity of the considered probiont strains in the additive composition was studied on Escherichia coli and Staphylococcus aureus. Acid forming activity of the probiont strains was studied by determination of variety and number of organic acids produced by the considered microflora. Results: Experimental results demonstrated that the dry probiotic food additive satisfied the safety requirements, and its maximum storage period was 6 months. Conclusion: Combined usage of probiont strains in the additive promoted an increase in total titer of lactic bacteria, increase in inhibition zone of E. coli and S. aureus, as well as secretion of organic acids, which jointly provided high antibacterial properties. On the basis of used microflora as well as products of plant reprocessing, three-strain food additive was engineered and developed with high antagonistic, sorbing, and antitoxic properties. The used microorganism strains as natural forms of the gastrointestinal tract were able to survive here to the highest extent.